Large cation ethylammonium incorporated perovskite for efficient and spectra stable blue light-emitting diodes - Chu, Zema; Zhao, Yang; Ma, Fei; Zhang, Cai-Xin; Deng, Huixiong; Gao, Feng; Ye, Qiufeng; Meng, Junhua; Yin, Zhigang; Zhang, Xingwang; You, Jingbi (Nature communications, 2020)
Perovskite light-emitting diodes (PeLEDs) have showed significant progress in recent years; the external quantum efficiency (EQE) of electroluminescence in green and red regions has exceeded 20%, but the efficiency in blue lags far behind. Here, a large cation CH 3 CH 2 NH 2 + is added in PEA 2 (CsPbBr 3 ) 2 PbBr 4 perovskite to decrease the Pb–Br orbit coupling and increase the bandgap for blue emission. X-ray diffraction and nuclear magnetic resonance results confirmed that the EA has successfully replaced Cs + cations to form PEA 2 (Cs 1- x EA x PbBr 3 ) 2 PbBr 4 . This method modulates the photoluminescence from the green region (508 nm) into blue (466 nm), and over 70% photoluminescence quantum yield in blue is obtained. In addition, the emission spectra is stable under light and thermal stress. With configuration of PeLEDs with 60% EABr, as high as 12.1% EQE of sky-blue electroluminescence located at 488 nm has been demonstrated, which will pave the way for the full color display for the PeLEDs. Blue light-emitting diodes (LEDs) are critical for displays. Employing a large organic cation into a quasi-two dimensional perovskite with green emission, Chu et al. achieve LEDs exhibiting a high external quantum efficiency of 12.1% and stable spectra in the sky-blue region.